Global Imbalances Before and After the Global Crisis - Servén, Luis; Nguyen, Ha (2012)
This paper surveys the academic and policy debate on the roots of global imbalances, their role in the inception of the global crisis, and their prospects in its aftermath. The conventional view holds that global imbalances result primarily from unsustainably high demand for goods in the United States and other rich countries, and that their impending correction must involve major United States trade adjustment and dollar depreciation -- although recent literature argues that their extent may be dampened by financial adjustment effects. In contrast, an alternative view portrays global imbalances as the equilibrium result of asymmetries in world asset demand and supply. Absent changes in the deep determinants of these, global imbalances can persist. International capital flow patterns before and during the crisis lend support to the equilibrium view. The paper also examines different hypotheses proposed in the literature on the role of global imbalances in the generation and propagation of the financial crisis. On the whole, the evidence suggests that global imbalances were not among the major causes of the crisis. Lastly, the paper assesses alternative scenarios about the future of global imbalances, considering in particular their potential consequences for developing countries, and the policy measures that these might adopt to enhance their growth prospects in a changing global equilibrium.